Mixed selectivity encoding and action selection in the prefrontal cortex during threat assessment. (April 2018) - Grunfeld, Itamar S; Likhtik, Ekaterina
Highlights: The medial prefrontal cortex uses mixed selectivity to encode emotional stimuli. PL and IL show action selection for conditioned motor inhibition and excitation. BLA and vHPC input contribute to mixed selectivity encoding in mPFC. Prelimbic-mediated behaviors are inhibited when the Infralimbic cortex is active. Abstract : The medial prefrontal cortex (mPFC) regulates expression of emotional behavior. The mPFC combines multivariate information from its inputs, and depending on the imminence of threat, activates downstream networks that either increase or decrease the expression of anxiety-related motor behavior and autonomic activation. Here, we selectively highlight how subcortical input to the mPFC from two example structures, the amygdala and ventral hippocampus, help shape mixed selectivity encoding and action selection during emotional processing. We outline a model where prefrontal subregions modulate behavior along orthogonal motor dimensions, and exhibit connectivity that selects for expression of one behavioral strategy while inhibiting the other.